Speaking Ability of International Class Students of PGSD 2019 of Universitas Negeri Padang - Arsil Firmani; An Fauzia Rozani Syafei (Universitas Negeri Padang, 2023)
This research aimed to find out the speaking ability of students of PGSD international class along with the type of speaking difficulty found by the students. The researcher chose year 2019 of PGSD international class as the sample consists of 20 students. A speaking test in the form of interview from UPT Bahasa Universitas Negeri Padang was used in collecting the data. As the result, the speaking ability of the students were 70% fair and 30% very poor. 14 out of 20 students were in fair and 6 out of 20 were in very poor. Then, comprehension is in 23,6% as the highest percentage of students’ kind of difficulty. It is suggested to the lecturers in international class of PGSD 2019 to provide the students some extra classes of English so that they can perform the better speaking ability during the use of English as the medium in the class.